DESMOSOME CELL - CELL CONNECTIVITY - A REVIEW - Pradeep, Malavika; Santhanam, Archana; S., Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
Desmosomes can be defined as intermediate junctions that tether intermediate filaments to the plasma membrane. When the function of desmosomal protein is altered, it can cause tissue fragility, which then leads to significant clinical consequences. Desmosomes can be differentiated into 3 morphologically identifiable zones, namely (i) extracellular core region (ii), outer dense plaque (iii), and inner dense plaque. The members of the cadherin superfamily include desmogleins and desmocollins, which mediate adhesion at desmosomes. Desmosomes are dynamic structures that are involved in the contribution of cellular processes beyond cell adhesion and are also quite critical when it comes to the maintenance of cell adhesion. Desmosomes are also subject to dynamic regulation and undergo continual turnover. There are four isomers of desmoglein (Dsg 1-4) and three isoforms of desmocollin (Dsc 1-3) found in humans. Calcium-dependent assembly adhesion is seen in desmosomes. Pemphigus is a class of disease where the autoantibodies target desmosomal cadherins, Dsg 1 and Dsg 3. The members of the armadillo gene family, Plakoglobin and Plakophilin, are included in the desmosomal plaque. The plakoglobin, plakophilin, and desmoplakin associate the cadherin cytoplasmic tails. Alteration in desmosomal protein function leads to tissue fragility with significant clinical consequences.